Water Quality Assessment of Rivers in Aquatic Eco-environmental Function Regions in Changzhou City - WANG Xuesong; ZHANG Ge; LI Ying; XU Jinqian; CAI Yongjiu (Renmin Zhujiang)
In 2018,57 monitoring sections were arranged for a quarterly water quality survey in Changzhou,which can help grasp the water quality of 13 aquatic eco-environmental function regions.The current situation,characteristics of spatial heterogeneity,and seasonal changing laws of main water quality indicators are evaluated by multiple methods such as the water quality grade analysis,comprehensive water quality identification index (WQII) method,redundancy analysis,and principal component analysis.In this way,we can explore the major influencing factors of water quality.The results are as follows:① In 2018,the water quality of rivers in Changzhou City was mainly classified as Grade IV according to the Environmental Quality Standards for Surface Water (GB 3838—2002),which indicates the poor water quality.② The results show significant spatio-temporal difference in the concentration of main water quality indicators,and the water quality in the western hills is better than that in the eastern plains.The grade of water quality is higher in summer and autumn than in spring and winter.③ From the perspective of aquatic eco-environmental function regions,the water quality of III-09 (ecologically Grade III), IV-02 (ecologically Grade IV),and IV-03 (ecologically Grade IV) regions in the eastern urban area is poor,while the water quality of I-02 (ecologically Grade I), II-01 (ecologically Grade II),III-08 (ecologically Grade III) regions in the west is good.The grades of aquatic eco-environmental function regions are highly consistent with the water quality,which proves that the function regions can provide scientific reference for the monitoring, assessment,and environmental management of water quality.④ The redundancy analysis shows that the land for construction is the main influencing factor in the deterioration of water quality.The increase in the relative proportion of arable land and the decrease in the aquatic area closely correlate with the deterioration of water quality when the scale is over 2,000 m.⑤ The principal component analysis indicates that the five-day biochemical oxygen demand,COD,and permanganate index have high interpretation rates.This shows that the water quality of rivers in Changzhou City is mainly affected by organic pollution and eutrophication. The threat factors of water quality in different grades of aquatic eco-environmental function regions are different.The ecologically Grade IV area is mainly affected by ammonia nitrogen and total phosphorus,while the ecologically Grade III and Grade II areas are mainly affected by total nitrogen,COD,and five-day biochemical oxygen demand.The study shows that the water quality of rivers in Changzhou City is poor,and the water quality is mainly influenced by organic pollution and eutrophication.Obvious spatio-temporal difference exists as the water quality in the west is superior to that in the east,which is consistent with the function regions.